3D Printing of Pharmaceuticals and Drug Delivery Devices - Lamprou, Dimitrios A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The 3D printing (3DP) process was patented in 1986; however, only in the last decade has it begun to be used for medical applications, as well as in the fields of prosthetics, bio-fabrication, and pharmaceutical printing. 3DP or additive manufacturing (AM) is a family of technologies that implement layer-by-layer processes in order to fabricate physical models based on a computer aided design (CAD) model. 3D printing permits the fabrication of high degrees of complexity with great reproducibility in a fast and cost-effective fashion. 3DP technology offers a new paradigm for the direct manufacture of individual dosage forms and has the potential to allow for variations in size and geometry as well as control dose and release behavior. Furthermore, the low cost and ease of use of 3DP systems means that the possibility of manufacturing medicines and medical devices at the point of dispensing or at the point of use could become a reality. 3DP thus offers the perfect innovative manufacturing route to address the critical capability gap that hinders the widespread exploitation of personalized medicines for molecules that are currently not easy to deliver. This Special Issue will address new developments in the area of 3D printing and bioprinting for drug delivery applications, covering the recent advantages and future directions of additive manufacturing for pharmaceutical products.